PERANAN USROH DALAM GERAKAN IKHWANUL MUSLIMIN - HT, Hidayat (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2019)
Abstract : The Muslim Brotherhood or often referred to as Al-Ikhwan is an organization or movement in the Middle East, precisely in the Egyptian state founded by Hasan Al- Banna. The Muslim Brotherhood was able to withstand the pressures given by the ruling regime. The Brotherhood has experienced status as a prohibited organization, dissolution by the regime, banning legal political activities but then being able to rise again and appear on Egyptian political stage as a thrilling force. One of the Muslim Brotherhood's wasīīs to maintain their existence as an organization or movement by using usroh devices. This paper seeks to uncover the concept of usroh and the important role it plays in the Muslim Brotherhood movement. Usroh is a choice of movement strategy used by the Muslim Brotherhood. Usroh is a cell from a collection of cells that make up the Muslim Brotherhood congregation. Usroh is the smallest station of the missionary movement as a forum for tarbawī, jamā'i and ijtimā'i activities for its members and is at the foremost position in carrying out the mandate of da'wah. Usroh's existence is very urgent in a congregation because it can be a means of building solidity and solidarity, fostering loyalty and strengthening the values of spirituality (ruhiyah). Keywords: Muslim Brotherhood and Usroh